Reading Strategies in EFL Classrooms: Overcoming Obstacles in Drawing Conclusion and Prediction - Linta Wafdan Hidayah; Putri Alifatul Maulida; Selvi Rahmawati (Universitas Islam Negeri Palopo, 2026)
Drawing conclusions and predicting outcomes are essential inferential reading skills for English as a Foreign Language (EFL) learners. However, many students experience difficulties in applying these strategies due to low self-confidence, reliance on explicit information, and limited experience with inferential reading tasks. This study investigates the challenges faced by EFL students in drawing conclusions and making predictions during reading comprehension activities. A qualitative case study design was employed involving 30 second-semester university students enrolled in an Inferential Reading course at Universitas Islam Madura. Data were collected through classroom observations, semi-structured interviews, and inferential reading tasks, and were analyzed thematically using triangulation to ensure credibility. The findings reveal that students tend to avoid inferential reasoning because of fear of making mistakes, insufficient instructional modeling, and limited vocabulary knowledge. As a result, students rely heavily on literal comprehension and demonstrate passive engagement with texts. This study suggests that explicit instruction in inferential strategies, supportive classroom environments, collaborative reading activities, and formative assessments focusing on reasoning processes can enhance students’ confidence and inferential reading abilities. These findings provide pedagogical implications for improving reading instruction in EFL classrooms.